PENGARUH KINERIA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Simanihuruk, Peran (UNIKA Santo Thomas, 2011)
Indonesia country has a comparative advantage in producing oil, so the master sizeable international market for many commodities such as cocoa, rubber, tea, coï¬‚ee, pepper, vanilla, copra, crude palm oil, essential oils, tobacco and areca nut. In 2008, the stock price of the entire plantation companies listed on the Indonesia Stock Exchange (IDX) down. In 2009, there is one company that its stock price fell, while in 2010 there were two companies that share price fell. So the research problem is: